Facile synthesis of N, B-co-doped carbon dots with the gram-scale yield for detection of iron (III) and E. coli. (7th July 2020) - Zhang, Lixia; Zhang, Zishu; Gao, Zhiwen; Xie, Yan; Shu, Shuang; Ke, Yuee; Wang, Yu; Deng, Bin; Yu, Ruijin; Geng, Huiling
Abstract: A simple method was developed to prepare fluorescent nitrogen/boron-doped carbon dots (N, B-CDs) in the gram scale. The results showed that the CDs exhibited blue photoluminescence (PL) under 365 nm ultraviolet radiation and excitation-dependent emission. Heteroatoms entered the CDs to enhance the photochemical properties, and their positive properties can be attributed to the presence of guanidino group and functionalized with boronic acid for realizing their utilization in certain applications. These materials could be applied to monitor Fe 3+ via static PL quenching, yielding a limit of detection (LOD) of 0.74 μ M. Furthermore, the charged and boronic acid groups on the prepared N, B-CDs enabled their use as recognition elements to bind with the bacteria through electrostatic interaction and allowed covalent interactions to form the corresponding boronate ester with E. coli ( E. coli ) bacterial membrane. This method could satisfy a linear range of 10 2 –10 7 with LOD of 165 cfu ml −1 for E. coli . This method was applied for the determination of E. coli in tap water and orange juice samples, and satisfactory results were obtained.